Hubungan Pengetahuan, Sikap Dan Perilaku Pencegahan Penyakit Menular Seksual (PMS) Dan HIV/AIDS Dengan Pemanfaatan Pusat Informasi Konseling Remaja (PIK-R) Pada Remaja SMKN Tandun Kabupaten Rokan Hulu - Wulandari, Sri (Jurnal Martenity and Neonatal, 2015)
Background: STDs have a huge impact on the sexual and reproductive health in the worldwide. Sexually Transmitted Diseases (STDs) is one of the important factors that increase HIV transmission. If there is no proper policy in the fight against STDs, then reduce the transmission of HIV would be difficult. The main strategy for the control of STDs is through improved prevention programs. International studies and also studies in Indonesia have shown that the provision of reproductive health education in schools will produce a life of sexual behavior more responsible and safer sex. UNAIDS states, education on HIV / AIDS is most effectively done through health and sex education in schools or through peer education. The study design was quantitative with in-depth interview cross-sectional design with sample size was 140 adolescents SMKN Tandun. Sampling used simple random sampling and purposive sampling. Data analysis used univariable analysis, bivariate with chi-square statistics test p <0.05 and 95% CI significance level, and multivariable with logistic regression. The percentage of adolescents who utilize PIK-R of 33.6%. Multivariable analysis revealed that there is a significant relationship between the utilization of PIK-R with the knowledge and OR 2.67 (95% CI 1.07-6.63), and the attitude of OR value of 3.67 (95% CI 1:58-8:50), 3.16 behavioral OR (95% CI 1.30-7.69). Exposure of information indicated p-value was 0.010, and the influence of peers was p-value was 0.858 to the utilization of PIK-R. Multivariable logistic regression: variables of knowledge, attitude and behavior towards PIKR can predict utilization of PIK-R by 18%. Barriers to the utilization of PIK-R by shy teens, time of service, lack of communication officer, the room was uncomfortable.